Loss of c-Met signaling sensitizes hepatocytes to lipotoxicity and induces cholestatic liver damage by aggravating oxidative stress - Gómez-Quiroz, Luis E.; Gaiser, Timo (Toxicology, 2016)
Recent studies confirmed a critical importance of c-Met signaling for liver regeneration by modulating redox balance. Here we used liver-specific conditional knockout mice (MetKO) and a nutritional model of hepatic steatosis to address the role of c-Met in cholesterol-mediated liver toxicity. Liver injury was assessed by histopathology and plasma enzymes levels. Global transcriptomic changes were examined by gene expression microarray, and key molecules involved in liver damage and lipid homeostasis were evaluated by Western blotting. Loss of c-Met signaling amplified the extent of liver injury in MetKO mice fed with high-cholesterol diet for 30days as evidenced by upregulation of liver enzymes and increased synthesis of total bile acids, aggravated inflammatory response and enhanced intrahepatic lipid deposition. Global transcriptomic changes confirmed the enrichment of networks involved in steatosis and cholestasis. In addition, signaling pathways related to glutathione and lipid metabolism, oxidative stress and mitochondria dysfunction were significantly affected by the loss of c-Met function. Mechanistically, exacerbation of oxidative stress in MetKO livers was corroborated by increased lipid and protein oxidation. Western blot analysis further revealed suppression of Erk, NF-kB and Nrf2 survival pathways and downstream target genes (e.g. cyclin D1, SOD1, gamma-GCS), as well as up-regulation of proapoptotic signaling (e.g. p53, caspase 3). Consistent with the observed steatotic and cholestatic phenotype, nuclear receptors RAR, RXR showed increased activation while expression levels of CAR, FXR and PPAR-alpha were decreased in MetKO. Collectively, our data provide evidence for the critical involvement of c-Met signaling in cholesterol and bile acids toxicity.